Mobile Application For SJK (C) Pei Hua - Abd Ishak, Suhaimi; Kat Yi Yun, (Applied Information Technology And Computer Science, 2020)
Mobile application for Library SJK (C) Pei Hua is an Android based application that is developed to provide a platform for easy accessed of information by students through mobile application. The notification is not in the current system and user will tend to forget the deadline of returning book if they lost the receipt and does not know the exact date of returning book. At the end result of the project, librarians in SJK (C) Pei Hua, which is act as the administrator of this mobile application are able to manage the application in the administration site. Users are able to search books and may explore more information about the news and upcoming events that will held on SJK (C) Pei Hua. The system will show the reminder notification about the due date of returning books. Users are able to send messages or feedback to the administrator through the Contact Us form in this application.